Wogonin a Promising Component of Scutellaria baicalensis: A Review on its Chemistry, Pharmacokinetics and Biological Activities - Maha Hassanin; Mai Tolba; Marianne Tadros; Mohamed Elmazar; Abdel-Nasser Singab (Ain Shams University, 2019)
Scutellaria baicalensis Georgi (Huang-Qin or Chinese skullcap) is a native medicinal plant in China that is commonly used for the treatment of seizures, viral infections, and cancer. The numerous pharmacodynamics of this plant is referred to as its rich content of flavones (baicalin and wogonoside) and their corresponding aglycones (baicalein and wogonin). Wogonin is one of the most extensively investigated active components of Scutellaria baicalensis. A multitude of preclinical studies indicated that wogonin possesses many pharmacological activities including anti-inflammatory, antioxidant, cytotoxic, neuroprotective, antidiabetic and antiviral effects. However, studies regarding the toxicity profile of wogonin are lacking. This review focuses on the recently published data regarding the chemistry and the pharmacokinetic profile of wogonin. Moreover, it highlights some of wogonin's well documented biological activities such as cytotoxic, neuroprotective, antidiabetic and antiviral activities. The information in this review encourages further investigations to elucidate the wogonin's full toxicological profile for verification of the safety of wogonin and the determination of the maximal tolerable dose (MTD) to be able to extrapolate wogonin's benefits to the clinical setting.